2022
DOI: 10.3389/fmicb.2022.1070276
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of human brucellosis among the tribal and non-tribal population residing in an eastern state of India: Findings from the state-wide serosurvey

Abstract: BackgroundBrucellosis is a neglected zoonotic disease found predominantly in lower- and middle-income countries (LMICs), causing significant public health concern in India. The objective of this study was to assess the prevalence of human brucellosis in Odisha, India among community members involved in animal husbandry as a common practice.MethodThis cross-sectional study included 817 adult participants from 11 districts in Odisha. Four districts from the Northern division, four districts from the Central divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The combination of doxycycline with rifampin or an aminoglycoside is effective in the treatment of brucellosis in humans. A retrospective study, such as this one, provides useful information regarding the trend of disease that can help formulate policies and strategies for the control and eradication of this occupationally hazardous disease, which is otherwise neglected [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of doxycycline with rifampin or an aminoglycoside is effective in the treatment of brucellosis in humans. A retrospective study, such as this one, provides useful information regarding the trend of disease that can help formulate policies and strategies for the control and eradication of this occupationally hazardous disease, which is otherwise neglected [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brucellosis is a significant public health concern in India because of its high seroprevalence in humans; however, epidemiological data are lacking. A recent survey showed that the overall seroprevalence of brucellosis was 11.37% in Meghalaya [ 28 ], 29.73% in Sambalpur District, and 4.44% in Mayurbhanj District [ 29 ]. The annual median losses due to human brucellosis were estimated to be Rs 627.5 million among adults and Rs 185.0 million among children [ 30 ].…”
Section: Asiamentioning
confidence: 99%